Mentoring practise during practicum: The perspectives of Malaysian pre-service English language teachers - Intan Safinas Mohd Ariff Albakri; Noriah Ismail; Rudi Hartono; Mohd Haniff Mohd Tahir; Maria Shu Hong Bee Abdullah; Anida Sarudin; Noraini Zulkepli (Universitas Syiah Kuala, 2021)
This study investigates the issues in mentoring practise based on pre-service English language teachers’ perspectives about their mentoring experience. This study involved 56 pre-service teachers who had completed their practicum. The study used a quantitative data collection method whereby a questionnaire survey was distributed to the research participants. The data from the questionnaire was then analysed by using SPSS to generate descriptive statistics for item analysis. The findings were discussed based on five mentoring factors which are personal attributes, system requirements, pedagogical knowledge, modelling, and feedback. The findings show that modelling and pedagogical knowledge received among the lowest mean scores indicating the moderate satisfactory level of mentoring experience received by the pre-service teachers. The data also shows considerable issues in mentoring quality in terms of pedagogical knowledge. Based on the findings, one of the most crucial issues to be addressed was equipping mentor teachers with the knowledge and skill of mentoring. The mentor teachers need to be given a course and guidance on the key aspects of mentoring. A mentoring manual must be given to the mentors in order to guide them in providing quality and structured mentoring.